Construction of a library and english basic manual for students from the Multigrade Cochea Arriba Elementary School - González Arjona, Celideth Marissa (UDELAS, 2011)
The present document shows the reality that a mulilevel school faces, its lication, antecentes, the basic needs and the reasons why it was decided to do this community project. Here we can see the importance of providing students with the necessary tools so that they can achieve the minimum essentials in the knowledge of english.